Spatio-Temporal Projections of the Distribution of the Canopy-Forming Algae Sargassum in the Western North Pacific Under Climate Change Scenarios Using the MAXENT Model - Sun Kyeong Choi; Young Baek Son; Hyun Woo Jeong; Seonggil Go; Sang Rul Park (Biology)
Canopy-forming algae play an important role in coastal ecosystems because these species are highly productive and provide habitats and shelter for numerous marine organisms. Sargassum is the main genus of canopy-forming algae in the western North Pacific, but despite the importance of their ecological role, studies on the changes in their distribution are still scarce. Based on the present distribution of four Sargassum species, this study predicted the geographic distribution of future habitats (2030s, 2060s, and 2090s) under three Shared Socioeconomic Pathway (SSP) scenarios. The environmental variables predicted from the sixth phase of the coupled model intercomparison project (CMIP6) had different impacts depending on the species, with current velocity and water temperature showing high contributions in all four species. According to the projections, three Sargassum species (S. horneri, S. macrocarpum, and S. patens) are expected to maintain a higher habitat suitability index (HSI) and suitable habitat (MAXENT ≥ 0.4) through the 2090s under the SSP1-1.9 scenario. However, under the SSP2-4.5 and SSP5-8.5 scenarios, the HSI of the species is projected to gradually decrease in the southern coastal waters of the Korean peninsula and increase in the East Sea (North Korea), with these results intensifying under the SSP5-8.5 scenario. On the other hand, S. piluliferum was found to increase its HSI and habitat under the highest emission scenarios. All Sargassum species are predicted to shift northward from 0.8° N to 3.8° N by the 2090s under the SSP5-8.5 scenario. Although many marine protected areas exist off the coasts of South Korea and Japan, suitable Sargassum habitats were found to be located within protected reserves between 47.1% and 61.2%, depending on the scenario. These findings on Sargassum provide distributional predictions for ecological conservation strategies and provide new evidence for the need for climate change efforts.